Apriorismo, epigénesis y evolución en el transcendentalismo kantiano - Eugenio Moya (Revista de Filosofia, 2006)
In this article, I defend the idea that Kant’s interest in an emergent science in the 18th century as the Embriology (especially in the concept of epigenesis) allows to deepen in a soft naturalization of Kant’s trancendental idealism, as well as to justify the validity of a priori knowledge.